2008
DOI: 10.1590/s0074-02762008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with epimastigotes of different strains of Trypanosoma rangeli protects mice against Trypanosoma cruzi infection

Abstract: In our laboratory, we have developed a model of vaccination in mice with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 14 publications
(17 reference statements)
0
21
0
6
Order By: Relevance
“…We observed that previously vaccinated mice showed very low parasitaemia, high survival rates and an absence of histological and autoimmune lesions, while mice that were only infected showed high parasitaemia, high mortality and severe histopathological alterations in the heart, skeletal muscle, spleen and liver [13,22,23] . For histological studies, mice from each group: vaccinated with T. rangeli and afterward challenged with T. cruzi (V) (n = 6) and non-vaccinated but infected with T. cruzi (I) (n = 6), were killed with ether anesthesia.…”
Section: Minireviewmentioning
confidence: 86%
See 1 more Smart Citation
“…We observed that previously vaccinated mice showed very low parasitaemia, high survival rates and an absence of histological and autoimmune lesions, while mice that were only infected showed high parasitaemia, high mortality and severe histopathological alterations in the heart, skeletal muscle, spleen and liver [13,22,23] . For histological studies, mice from each group: vaccinated with T. rangeli and afterward challenged with T. cruzi (V) (n = 6) and non-vaccinated but infected with T. cruzi (I) (n = 6), were killed with ether anesthesia.…”
Section: Minireviewmentioning
confidence: 86%
“…Similar results were obtained with two strains of T. rangeli from different origins, isolated in Colombia and Brazil, which revealed that the capacity to protect mice against lethal infection by T. cruzi is a characteristic common to different strains of T. rangeli. This result represents a clear advantage for the future preparation of possible vaccines for animal or human use [24] . On the other hand, it was demonstrated [25] that, in the acute period of experimentally infected mice, T. cruzi induces a response that presents different patterns in each different immune system compartment, splenomegaly, lymphoid subcutaneous tissue expansion, persistent polyclonal activation of lymphocyte T and B, and at the same time, thymus and mesenteric node atrophy.…”
Section: Minireviewmentioning
confidence: 93%
“…34 Similarly, immunization with live T. rangeli, a related parasite species non-pathogenic in humans, can also provide some cross-reactive immunity and partial protection, possibly due to homologous antigens. [35][36][37] However, these approaches raise the issues commonly associated with live vaccines, i.e., safety and the challenges associated with their large-scale production and distribution. Nonetheless, there is a renewed interest in a live attenuated vaccine approach and recent studies have described the generation of T. cruzi mutants for specific genes such as LYT1 or ECH1 and 2, which can provide good protection against infection in mice, including through oral administration.…”
Section: Current Status Of Vaccine Researchmentioning
confidence: 99%
“…A expressão de antígenos comuns a essas duas espécies tem sido associada à proteção induzida em animais infectados com T. rangeli quando desafiados com T. cruzi (PALAU et al, 2003;BASSO et al, 2007BASSO et al, , 2008. Além disso, existem evidencias de uma aparente diminuição da severidade da Doença de Chagas quando ocorre na presença de T. rangeli HUDSON et al, 1988;BASSO et al, 2007BASSO et al, , 2008).…”
Section: Estudos Recentes Desenvolveram Técnicas Imunológicas (Tesa-bunclassified
“…Além disso, existem evidencias de uma aparente diminuição da severidade da Doença de Chagas quando ocorre na presença de T. rangeli HUDSON et al, 1988;BASSO et al, 2007BASSO et al, , 2008). …”
Section: Estudos Recentes Desenvolveram Técnicas Imunológicas (Tesa-bunclassified